2023
DOI: 10.1021/acsomega.3c06768
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Practical DNA Quantification Method for DNA-Encoded Library Synthesis

Hangke Ma,
Zhaomei Sun,
Lijun Xue
et al.

Abstract: Over the past three decades, DNA-encoded library (DEL) technologies have become one of the most relevant strategies for hit-finding. Recent advances in synthetic methodologies for DNA-encoded libraries rendered the increased chemical space available, but it is unknown how every variety of chemistry affects DNA’s integrity. Available assays to quantify DNA damage are restricted to electrophoresis, ligation efficiency, and mostly qPCR quantification and sequencing, which may contain predisposition and inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The results indicated that only negligible DNA damage under the standard reaction conditions could be observed for both sulfide and sulfoximine formation (see section 8.1 and 8.2 of the Supporting Information for details). In parallel, we subjected a capped substrate with no predicted reactivity to the standard reaction conditions as a control experiment, and the results clearly indicated that the DNA conjugate remained intact throughout the entire synthetic route, hereby further validating the integrity of encoding DNA tags (see section 8.7 of the Supporting Information for details).…”
mentioning
confidence: 70%
“…The results indicated that only negligible DNA damage under the standard reaction conditions could be observed for both sulfide and sulfoximine formation (see section 8.1 and 8.2 of the Supporting Information for details). In parallel, we subjected a capped substrate with no predicted reactivity to the standard reaction conditions as a control experiment, and the results clearly indicated that the DNA conjugate remained intact throughout the entire synthetic route, hereby further validating the integrity of encoding DNA tags (see section 8.7 of the Supporting Information for details).…”
mentioning
confidence: 70%
“…To our delight, the results indicated that the reaction conditions did not cause any evident DNA damage. As well, a capped substrate with no expected reactivity was subjected to the typical coupling conditions as a control experiment, and the results demonstrated that the DNA oligo conjugate remained intact throughout the reaction process, thereby further verifying the DNA oligos’ integrity (see SI S212–S223 for details) …”
mentioning
confidence: 99%
“…Moreover, a capped substrate with no predicted reactivity was exposed to the standard reaction conditions as a control experiment, and the results demonstrated that the DNA oligo conjugate remained intact throughout the reaction process, thereby further confirming the integrity of encoding DNA tags (see ESI† for details). 29…”
mentioning
confidence: 99%